Implementation And Assessment Of Knowledge Based Systems In Various Engineering Courses - Tumkor, Serdar; Sekmen, Ali; Pecen, Recayi; Zora, Ayhan; Fidan, Ismail (ASEE Conferences, 2020)
Comment: 13 pages